Zonally heated tooling for moulding complex and highly tapered composite parts - Maes, Vincent K.; Radhakrishnan, Arjun; Lombetti, Diego; Kratz, James (Frontiers in Materials, 2023)
Curing of composite material parts often rely on slow cure cycles to manage exotherms and avoid hot or cold spots in the part. This is especially true for larger, thicker and/or geometrically complex parts, which suffer from unevenness in heating between different regions of the part stemming from thickness variations and made worse by the use of convection heating in ovens and autoclaves. An alternative technology for moulding is using heated tooling, which improves the energy efficiency of the process but can also significantly increase the tooling costs. However, the true power of heated tooling is in the ability to tailor the temperature profile in different regions. By introducing zonal heating, significantly faster process cycles can be achieved, hence improving production rates. Using cure simulation, two identical components are analysed, one part produced using convection heating (i.e. oven) and the second made using direct heating (i.e. heated tooling). The zonal approach was tuned based on numerical models and shows a reduction 17.5% in terms of cure time and the experimental trials found an approximate 45% reduction in energy consumed.